Local Authority Level Source Apportionments of PM2.5Concentrations based on the CAPSS 2016: (VII) Seoul - Bae, Minah; Kim, Eunhye; You, Seunghee; Son, Kyuwon; Kang, Yoon Hee; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2021)
The Comprehensive Air quality Model with eXtensions with Particulate Source Apportionment Technology (CAMx- PSAT) was simulated to quantify the self- and neighboring provincial contributions to the concentrations of PM2.5and its compositions in Seoul during the whole year of 2016. The domestic and foreign contributions to the annual mean PM2.5concentration in Seoul were 11.8 and 15.8 μg/m3, respectively during the year. The individual contribution of Seoul, Gyeonggi, Incheon, and Chungnam were 4.5, 3.3, 1.1, and 1.5 μg/m3, respectively. While Seoul has the highest NOxemission density among 17 provinces in South Korea, its self-contribution to nitrate was 0.3 μg/m3, which is lower than the contributions of Gyeonggi (1.0 μg/m3) and Chungnam (0.5 μg/m3). The contribution of NOxemissions released from Seoul to nitrate over Yeoju and Guri in Gyeonggi, the downwind areas of Seoul, was 0.4 μg/m3which was higher than the self-contribution. While sulfate in Seoul was largely attributable to the emissions from the upwind foreign countries, the contribution of Chungnam was 0.4 μg/m3, which is higher than the sum of the contributions of Seoul, Gyeonggi, and Incheon. In cases of ammonium and Primary PM2.5(PPM2.5), the self-contributions were dominant and as high as 1.6 and 2.5 μg/m3, respectively. The results of this study imply that collaboration on air quality management among Seoul and the neighboring provinces is imperative to meet the national ambient air quality standard for the annual mean PM2.5(15 μg/m3).
Keywords: Foreign and domestic contributions; Inter-provincial contribution; Nitrate; PM2.5contribution; Seoul